2015
DOI: 10.1507/endocrj.ej14-0590
|View full text |Cite
|
Sign up to set email alerts
|

A case of insulinoma with non-alcoholic fatty liver disease: Roles of hyperphagia and hyperinsulinemia in pathogenesis of the disease

Abstract: Abstract. Nonalcoholic fatty liver disease (NAFLD) is a serious health-related condition all over the world; the number of patients is increasing in Asian countries including Japan. Better understanding of its pathophysiology is required to develop effective therapeutics, as patients may go on to develop non-alcoholic steatohepatitis and hepatocellular carcinomas. While NAFLD is believed to be associated with metabolic risk factors such as obesity, diabetes, and dyslipidemia, its etiology remains largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In addition, our case did not show any increased appetite or body weight gain, although these are also characteristic symptoms of insulinoma ( 16 , 21 ). AEDs can also cause a masking effect on hunger and weight gain, possibly through a reduced appetite ( 10 ).…”
Section: Discussionsupporting
confidence: 39%
“…In addition, our case did not show any increased appetite or body weight gain, although these are also characteristic symptoms of insulinoma ( 16 , 21 ). AEDs can also cause a masking effect on hunger and weight gain, possibly through a reduced appetite ( 10 ).…”
Section: Discussionsupporting
confidence: 39%
“…Previous studies have shown that the median time to a diagnosis is 24 months, with a range of up to 30 years (12). A delayed diagnosis of insulinoma can progressively induce coma or death (7,8,13) and remains a clinical issue (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…The intake of fructose is recognized as a risk factor for NAFLD, and some types of fruit are fructose-rich foods [187]. A case report of a 33-year-old male with insulinoma and hypoglycemia for 4 years showed that overeating of fruits, especially the fruits rich in fructose, might exacerbate histological changes of NAFLD [188]. Therefore, the dietary recommendations of fruit intake for the fatty liver population need to be considered thoroughly and carefully.…”
Section: Safety and Application Issue Of Fruits And Their Bioactivementioning
confidence: 99%